Lupin seed hydrolysate promotes G-protein-coupled receptor, intracellular Ca2+ and enhanced glycolytic metabolism-mediated insulin secretion from BRIN-BD11 pancreatic beta cells - Tapadia, Mrunmai; Carlessi, Rodrigo; Johnson, Stuart; Utikar, Ranjeet; Newsholme, Philip (Molecular and cellular endocrinology, 2019)
Lupin seed proteins have been reported to exhibit hypoglycaemic effects in animals and humans following oral administration, however little is known about its mechanism of action. This study investigated the signalling pathway(s) responsible for the insulinotropic effect of the hydrolysate obtained from lupin (Lupinus angustifolius L.) seed extracts utilizing BRIN-BD11 β-cells. The extract was treated with digestive enzymes to give a hydrolysate rich in biomolecules ≤7 kDa. Cells exhibited hydrolysate induced dose-dependent stimulation of insulin secretion and enhanced intracellular Ca2+ and glucose metabolism. The stimulatory effect of the hydrolysate was potentiated by depolarizing concentrations of KCl and was blocked by inhibitors of the ATP sensitive K+ channel, Gαq protein, phospholipase C (PLC) and protein kinase C (PKC). These findings reveal a novel mechanism for lupin hydrolysate stimulated insulin secretion via Gαq mediated signal transduction (Gαq/PLC/PKC) in the β-cells. Thus, lupin hydrolysates may have potential for nutraceutical treatment in type 2 diabetes. •Lupin hydrolysate promotes insulin secretion in pancreatic β cells.•Mechanism involves activation of a Gαq-PLC-PKC pathway.•Hydrolysate-induced effects are glucose permissive and involves enhanced glycolysis.•Hydrolysate promotes membrane depolarisation and release of intracellular Ca2+.